Evaluation Of The E-Commerce Websites In Different Stages Of The Purchase Cycle: An Iranian Perspective - Shemirani, Nazila Irani (2011)
In this research, some important variables and a framework for evaluation of commercial websites have been introduced and studied. A number of commercial and service companies which are active in E-commerce including banks, supermarkets chains and transportation agencies have been studied as statistical society.